Paediatric palliative care for the generalist - Julia F. Ambler; Christoffel H. Bell (South African Family Practice)
Palliative care has been defined as ‘the active holistic care of individuals across all ages with serious health-related suffering due to severe illness, and especially of those near the end of life’. Unfortunately, palliative care and especially paediatric palliative care remain a neglected area of medicine and are widely misunderstood, with few healthcare providers having any formal training in South Africa. To relieve health-related suffering, healthcare providers must understand that the field is not limited to end-of-life care for the terminally ill, and holistic care (physical, emotional, social and spiritual) should commence at the time of diagnosis of a serious illness. It is imperative that all healthcare providers develop the knowledge and skills to provide this essential care across all levels of care and disciplines. The article aims to raise awareness and show how to practically implement palliative care through case studies.